The Anti-tumor Effects of p-Coumaric Acid on Melanoma A375 and B16 Cells - Hu, Xue; Yang, Zihui; Liu, Wenjing; Pan, Zhaohai; Zhang, Xin; Li, Minjing; Liu, Xiaona; Zheng, Qiusheng; Li, Defang (Frontiers in Oncology, 2020)
Abstract Background: Existing research shows that p-coumaric acid (p-CA) can inhibit the proliferation of a variety of tumor cells in vitro. However, there are no reports on the anti-tumor effects of p-CA on melanoma cells. In this study, the inhibitory effects of p-CA on mouse melanoma B16 and human melanoma A375 cells are reported, and the related mechanisms are investigated. Methods: CCK-8 assay was used to detect the effects of p-CA on cell vitality, colony formation assay was used to observe the effects on cell proliferation, Hoechst 33258 staining was used to observe the morphology of apoptotic cells, flow cytometry was used to detect the effects on apoptosis and the cell cycle, and western blot was used to measure the levels of cell cycle- and apoptosis-related signaling pathway proteins. Results: p-CA significantly inhibits cell proliferation of A375 and B16 cells in a dose-dependent manner and obviously induced cell morphological changes. p-CA arrested A375 cells in the S phase by downregulating the cell cycle-related proteins Cyclin A and CDK2, and arrested B16 cells in the G0-G1 phase through downregulating the cell cycle-related proteins Cyclin E and CDK2. In addition, p-CA significantly promoted apoptosis of A375 and B16 cells. Furthermore, p-CA significantly upregulated the levels of Apaf1 and Bax and downregulated the levels of Bcl-2, and subsequently increased the levels of cytoplasmic cytochrome c (Cyto-c), cleaved caspase-3, and cleaved caspase-9, leading to apoptosis in A375 and B16 cells. Conclusion: p-CA can significantly inhibit the proliferation of human and mouse melanoma cells in vitro. Our research is a step in the development of anti-melanoma drugs.